Central African Republic : Poverty Reduction Strategy Paper; Preparation Status Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2008)
The status report on the Poverty Reduction Strategy Paper (PRSP) of the Central African Republic showed substantial progress. IMF staff welcomed peace and security consolidation and strong macroeconomic framework under the economic program. They emphasized the need for strengthening the linkages between some of the sectoral and national strategies. They stressed the need for a strategy for monitoring and evaluation of the system, and financing to implement the strategy. They concur that success of the PRSP will be a challenge amidst security issues and financial constraints.